2002
DOI: 10.1097/00000478-200206000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrative Astrocytomas With Granular Cell Features (Granular Cell Astrocytomas)

Abstract: Granular cell astrocytomas (GCAs) are rare, incompletely characterized infiltrative gliomas that contain a prominent component of granular cells. Such tumors can readily be mistaken for reactive conditions. We studied 22 cases to explore their morphologic spectrum, establish features useful in distinguishing GCA from nonneoplastic diseases, and to determine which parameters correlate with biologic behavior. Tumors occurred in 17 men and five women, ranging in age from 29 to 75 years, who presented mainly with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 16 publications
2
74
1
1
Order By: Relevance
“…3,9,12 Although no systematic studies of this tumor have been undertaken to date, GCTs of the neurohypophysis and pineal region, unlike GCAs of the cerebral hemisphere, seem to be typically benign and indolent despite occasional invasion and recurrence. 2,3,10 Follow-up evaluation in our case, in the 4 previously reported pineal cases, and in cases in all other intracranial localizations has shown that subtotal resection is effective for symptomatic tumors. 6,[8][9][10]12,15 The role of radiation therapy for this benign, slow-growing tumor remains unclear.…”
Section: 14supporting
confidence: 58%
“…3,9,12 Although no systematic studies of this tumor have been undertaken to date, GCTs of the neurohypophysis and pineal region, unlike GCAs of the cerebral hemisphere, seem to be typically benign and indolent despite occasional invasion and recurrence. 2,3,10 Follow-up evaluation in our case, in the 4 previously reported pineal cases, and in cases in all other intracranial localizations has shown that subtotal resection is effective for symptomatic tumors. 6,[8][9][10]12,15 The role of radiation therapy for this benign, slow-growing tumor remains unclear.…”
Section: 14supporting
confidence: 58%
“…28,29 Generally, the use of GFAP and macrophage-specific markers (eg, CD163) substantiates the glial lineage. However, CD68 immunoreactivity can be misleading since the lysosome-rich glioma cells are often positive and GFAP may be difficult to interpret in cases with high background staining.…”
Section: Granular Cell Glioblastomamentioning
confidence: 99%
“…One-year survival from GCA is reportedly 12% for high-grade GCA and 40% for low-grade GCA with extension to multiple cerebral lobes as seen in 35% of reported cases, may confer a poor prognosis despite a lack of aggressive histological features [150]. A study of 22 cases of GCAs (age range from 29 to 75 years) with a nearly 3 : 1 male : female ratio (17 men, 5 women) showed sheets of monomorphic round cells packed with eosinophilic, PAS-staining granules comprising 30-95% of cells [16]. Further more, this study demonstrated lymphocytic infiltration in 63% of cases, transition to infiltrating astrocytoma in 72% of cases, GFAP staining in 95% of tumours, common staining for S-100, KP-1, ubiquitin, and EMA, as well as MIB-1 index correlating with WHO grade.…”
Section: Granular Cell Astrocytomamentioning
confidence: 99%